(untitled) (Academia Journal of Medicine, 2026)
Oral cancer, predominantly oral squamous cell carcinoma (OSCC), remains a major global health burden with high morbidity and mortality rates due to late diagnosis and limited prognostic accuracy. Artificial Intelligence (AI), encompassing machine learning (ML) and deep learning (DL), has emerged as a transformative tool in healthcare, offering enhanced diagnostic precision, early detection, and prognostic prediction. AI-based systems analyze large datasets including clinical images, histopathological slides, radiographic scans, and molecular profiles to assist clinicians in decision-making. This review explores the applications of AI in oral cancer diagnosis and prognosis, highlighting recent advancements, advantages, limitations, and future perspectives.